IDENTIFYING PRIORITY ENVIRONMENTAL PROBLEMS IN ANDIJAN REGION (Multidisciplinary Journal of Science and Technology, 2023)
Changes in heart rate variability, identified using the cardiorhythmography method, indicate the severity of autonomic disorders, characterized by a sympathetic-parasympathetic imbalance with a predominance of sympathetic and suprasegmental autonomic influences, as well as a violation of adaptive mechanisms in patients with HT; these changes are more pronounced in females . In both groups there was a large percentage of patients with such symptoms - 89.1% and 80.7%, respectively, in MG and SG.